(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article highlights the problem of using English as an intermediary language in the classroom of Russian as a foreign language (RFL) with students of the English department at the university. It speaks about the expediency of using an intermediary language at the initial stage of learning, which, performing a number of important functions, allows for a comparative analysis of language facts, helps to overcome interference, and also focuses the attention of teachers of Russian as a foreign language on the need to speak English and create new nationally oriented textbooks on RFL, which is one of the main tasks of modern methods of teaching foreign languages.